IMPROVING STUDENTS’ WRITING SKILL USING BRAINSWRITING STRATEGY - Yulianti, Sintawati; Nuraeni, Siska; Parmawati, Aseptiana (PROJECT (Professional Journal of English Education), 2019)
Writing is one of important skill in English subject beside the other skills. To improve the students’ writing skill, we have to know what strategy is the most suitable for the students’. This research used Classroom Action Research. The research was on two cycles with total meetings were seven; three meetings were for tests, and four meetings were for treatment. Each cycle covered the step of planning, acting, observing, and reflecting. The population of this research was the Seventh Grade Students of SMP Pandu Nusantara in the academic year of 2018/2019 which consisted of 30 students. The average score of pretest was 45. After the implementation of brainswriting strategy in every cycle, the students’ writing skill score were getting better. It can be seen from the research of students’ average score Cycle 1 was 50 and Cycle was 71. It can be concluded that brainswriting strategy can improve students’ writing skill and improve writing classroom into a better situation.